The Effect of Project Based Learning Model in Information System Design Analysis Course on the Competence of Student Majoring in Informatics and Computer Engineering - Mustari Lamada; Shabrina Syntha Dewi; Dinda Nisrina Adisafira; Aulyah Zakilah Ifani (Information Technology Education Journal, 2025)
This research is conducted to analyze the impact of the Project Based Learning model in the Information Systems Design Analysis course on student competencies within the Department of Informatics and Computer Engineering. The study applies an ex post facto design combined with a descriptive-correlational quantitative method. Data collection involved interviews, questionnaires, and documentation. The independent variable is Project Based Learning, and the dependent variable is student competence. The total population consisted of 338 students, from which a sample of 77 was selected using the Slovin formula. The data were analyzed through descriptive statistics and simple linear regression analysis. The findings reveal that most students fall into the medium (34%) and high (21%) competence categories. The simple linear regression test produced a significance level of 0.000 (<0.05), indicating a significant effect between the independent and dependent variables. The correlation coefficient (R) of 0.760 signifies a strong connection between the variables, while the coefficient of determination (R²) of 0.578 demonstrates that 57.8% of the variance in student competence is explained by Project Based Learning, with the remaining 42.2% attributed to other external factors.